Estudio de prefactibilidad para la instalación de un taller productor de bolsos a base de fibra de hoja de piña (Ananas comosus) - Landauro Nieto, Treycy Estefani (2023)
This research project evaluated the commercial, technical, economic, financial and social feasibility of setting up a workshop to produce bags from pineapple leaf fiber to supply the market demand in Lima Metropolina, whose raw material is a residue from the pineapple harvest. The main problem that arises in this research is the need for an alternative product that does not come from animal origin. In addition, the environmental impact reflected in the high consumption of energy and water produced to produce animal leather is recognized. It also addresses the complications that pineapple farmers have in managing their crop residues, since the decomposition time limits the production of more plants and, for this reason, in some cases they resort to burning them. Based on the market study, the target public was defined as people between 18 and 55 years old, men and women, from Lima Metropolitana belonging to socioeconomic levels A and B. The demand for the project at the end of the period was determined to be 3 106 bags. With the evaluation of macro- and micro-localization, the location of the workshop was established as being in the department of Junín in the province of Satipo, considering different factors. The fabric production process begins with the selection of pineapple leaves, then to defibrate, washing, softening, drying, carding, needle punching, Spray and Print Bonding resin, heat setting, and finishing with calendering. The manufacturing process includes scribing, cutting, assembling, sewing, bagging, boxing and packaging. The total area of the workshop is 330 m2. Finally, the economic and financial evaluation yields a net present financial value of S/. 285 910,43 with an internal rate of return of 90,27%which indicates that the project is attractive and profitable.